(3aJM GdbQjH HTQM ehGgH GdeLjH aj NUGFU GdMHjHs - (3CMeO Hf Ydj Hf YeQ Hf UGdM, TgGH GdOjf, CHh GdfLGM Gdnepfjfj,J (B1172 (3g` s
(3ChdgG (B:s
(3CeG HYO deG jSQGddg JYGdi EJeGe efXheJi GdeSeGg HehGgH GdeLjH CTGQ Ydi ef ETGQJg Mce Gf CTQMgG TQMkG jaJM ebadgG s
(3BNQgG (B:s
(3hGf jLeYfG aj OGQ cQGeJg hJMjJge ajgG SdGe hBNQ OYhGge Cf GdMeO ddg QH GdYGdejf s
(3hcJHJ GdefXheI HGdMeQI hdPG ade JXgQ aj GdJUhjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B181 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B15s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B305 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B3389) s
Keywords: (3GdJGQjNs